2013
DOI: 10.1108/f-03-2012-0021
|View full text |Cite
|
Sign up to set email alerts
|

Occupant stimulus response workplace productivity and the vexed question of measurement

Abstract: Article information:To cite this document: Brian Purdey, (2013),"Occupant stimulus response workplace productivity and the vexed question of measurement", Facilities, Vol. 31 Iss 11/12 pp. 505 -520 Permanent link to this document: http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…As postulated by Bentler and Chou (1987) when a variable has four or more categories the results of statistical analysis are not significantly distorted. Yet use of standard deviation for Likert-scale data is not recommended and applying parametric statistical methods depends on establishing the normality of the data (Purdey, 2013). That is, parametric methods have underlying assumptions about normality and are permissible for use as long as variables meet the requirements about the shape of the distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As postulated by Bentler and Chou (1987) when a variable has four or more categories the results of statistical analysis are not significantly distorted. Yet use of standard deviation for Likert-scale data is not recommended and applying parametric statistical methods depends on establishing the normality of the data (Purdey, 2013). That is, parametric methods have underlying assumptions about normality and are permissible for use as long as variables meet the requirements about the shape of the distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The results of conducting the test for available data showed that all the variables in the dataset follow a non-normal distribution with the statistic for Shapiro-Wilk test ranging from 706 to 852 ( . This indicated that distributions of variables were not normal, thus use of parametric tests would culminate in distorted and misleading results (Ghasemi and Zahediasl, 2012;Purdey, 2013). Therefore, nonparamedic methods, which have no assumption regarding the distribution of data were utilised.…”
Section: Test Of Normality For Variablesmentioning
confidence: 99%
“…Due to its simplicity and popularity, the traditional Likert scale expanded into many variations of Likert‐type scales. These are commonly used in survey instruments designed for: measuring employee performance in the workplace (Purdey, ), communications research (Ryan, ), marketing research (Garland, ), political‐opinion research (Raaijmakers, van Hoof, ’t Hart, Verbogt, & Vollebergh, ), and psychometric research (Kulas & Stachowski, ). Its popularity, however, does not necessarily equate to its validity as a data collection method (Johns, ).…”
Section: Introductionmentioning
confidence: 99%
“…Debido a su simplicidad y popularidad, la escala Likert tradicional se expandió en muchas variaciones de escalas tipo Likert. Estos se usan comúnmente en instrumentos de encuestas diseñados para: medir el desempeño de los empleados en el lugar de trabajo (Purdey, 2013), investigación de mercado (Garland, 1991), e investigación psicométrica (Kulas & Stachowski, 2013).…”
Section: Métodounclassified